Multicultural Aspects of 21st Century Learning Using Digital Posters - Tiara Saputri Darlis; Fairuz Fairuz; Ninuk Lustiyantie; Uwes Anis Chaeruman (STKIP Singkawang, 2021)
21st century learning is learning that has the characteristics of being accessible, digital oriented, big data science and this learning is not limited to the distance of space and time. Poster presentation is a general form of educational information that is easily accessible, can be spread quickly with the presence of television, gadgets and the internet. This research method is descriptive qualitative method. While the research data in the form of educational posters. The results of this study are in the form of poster media requirements that are used as educational media, namely; 1) The content shall not contents that may offend the community/learning participants. The presented content shall be accepted by audience even with language and cultural differences. 2) The information shall be clear thus the message of the poster is well conveyed to audience with different cultural aspect. 3) The contents should be attractive, contains illustration images, and explanatory writings that make audience interested in the poster. 4) The development of digital poster with various version of local language may increase acceptabability among local language speaker.